Recent Advances in the Synthesis of Ibuprofen and Naproxen - Min-Woo Ha; Seung-Mann Paek (Molecules, 2021)
Herein, we review the recent progress in the synthesis of representative nonsteroidal anti-inflammatory drugs (NSAIDs), ibuprofen and naproxen. Although these drugs were discovered over 50 years ago, novel practical and asymmetric approaches are still being developed for their synthesis. In addition, this endeavor has enabled access to more potent and selective derivatives from the key frameworks of ibuprofen and naproxen. The development of a synthetic route to ibuprofen and naproxen over the last 10 years is summarized, including developing methodologies, finding novel synthetic routes, and applying continuous-flow chemistry.